DISCOVERY LEARNING METHOD THROUGH GEOGEBRA SOFTWARE TO IMPROVE MATHEMATICAL THINKING ABILITY OF POLYTECHNIC OF KEDIRI STUDENTS - Ratna Widyastuti; Fitria Nur Hamidah (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2017)
Mathematics learning not only trains students to do mathematical calculations but also trains critical, logical, analytical, and systematic thinking abilities. These four abilities are indicators of mathematical thinking ability. The ability of mathematical thinking gives contribution considerably in developing science and technology. One of mathematics subjects which was learned by Diploma III of informatics engineering study program is calculus mathematics. In the discret mathematics subject, there is a sub-material about picewise function, in programming language often known as logic function if ... than. This research used Classroom Action Research type (CAR). The research stages that had been made as follows: (1) determination of research focus; (2) action planning; (3) implementation of the action; (4) observation and interpretation; (5) analysis and reflection. The procedure of collecting research data was done through four stages, as follows: (1) conducting a written test before applying an action and written test after the implementation of each cycle action; (2) observation was done during learning process, (3) interview was done after final test implementation, (4) documentation in the form of photo. The findings of this research were the students' responses during the learning activities by using computer learning media were the passionate and active students in the group discussion activities as well as during the learning process. The results showed that learning which was designed appropriately with discovery steps could encourage students to improve their mathematical thinking ability. The use of computer media such as Geogebra could help students to achieve a better understanding which was related to material function through visual appearance. Students could identify the variable value of a function simply by putting a point on the graph which was formed.